Characterization of the gut microbiota of Kawasaki disease patients by metagenomic analysis - Kinumaki, Akiko; Sekizuka, Tsuyoshi; Hamada, Hiromichi; Kato, Kengo; Yamashita, Akifumi; Kuroda, Makoto (Frontiers in Microbiology, 2015)
Kawasaki disease (KD) is an acute febrile illness of early childhood. Previous reports have suggested that genetic disease susceptibility factors, together with a triggering infectious agent, could be involved in KD pathogenesis; however, the precise etiology of this disease remains unknown. Additionally, previous culture-based studies have suggested a possible role of intestinal microbiota in KD pathogenesis. In this study, we performed metagenomic analysis to comprehensively assess the longitudinal variation in the intestinal microbiota of twenty-eight KD patients. Several notable bacterial genera were commonly extracted during the acute phase, whereas a relative increase in the number of Ruminococcus bacteria was observed during the non-acute phase of KD. The metagenomic analysis results based on bacterial species classification suggested that the number of sequencing reads with similarity to five Streptococcus spp. (S. pneumonia, pseudopneumoniae, oralis, gordonii, and sanguinis), in addition to patient-derived Streptococcus isolates, markedly increased during the acute phase in most patients. Streptococci include a variety of pathogenic bacteria and probiotic bacteria that promote human health; therefore, this further species discrimination could comprehensively illuminate the KD-associated microbiota. The findings of this study suggest that KD-related Streptococci might be involved in the pathogenesis of this disease.